Kecenderungan Pola Asuh Orang Tua dalam Membina Kesantunan Anak di Jalan Swadaya, Kelurahan Cijantung - Farinda Trihardayanti Fatikha; Fitniwilis Fitniwilis (Journal on Education, 2024)
This research is based on the phenomenon of polite and impolite behavior in children influenced by various types of parental parenting. The research aims to determine the tendency of parental parenting in fostering children's politeness. This research uses a qualitative approach with a phenomenological type. The subjects of the study were parents consisting of three families, namely couples J and F (subject 1), couples S and SI (subject 2), and couples G and W (subject 3). The data collection methods used are observation, interviews, and documentation. The data that has been collected is triangulation to their respective neighbors. Data analysis uses a qualitative descriptive method, where each interview result is described and confirmed with triangulation results. The results of the analysis showed that subject 1 and subject 2 used permissive parenting. They tend to provide freedom without clear rules and boundaries, allowing children to explore and express themselves freely, but can also result in a lack of discipline and responsibility for children. Couples J and F (subject 1) were given the freedom to play gadgets without many rules, with the mother playing a more important role in regulating and reprimanding. Couples S and SI (subject 2) children were given gentle advice and freedom of play, with mothers more involved in building politeness. On the other hand, pairs G and W (subject 3) applied a more effective democratic parenting style in shaping children's politeness. This parenting style is characterized by open communication, clear arrangements, and strong emotional support. Parents teach politeness through direct example, verbal guidance, and religious values from an early age. Children are taught to respect others, control emotions and behave politely in various situations. This approach helps children grow up disciplined, independent, and have strong moral values.